First insight into the development of a new transcriptomic tool in French Corsica harbors. (November 2022) - Pillet, Marion; Evensen, K. Garrett; Marengo, Michel; Lejeune, Pierre; Poynton, Helen C.; Thomas, Hélène
Abstract: Coastal harbor areas are subjected to a myriad of contamination sources with largely unknown effects. Such complex chemical mixtures are difficult to monitor but transcriptomics is a promising approach for such biomonitoring. The present study was designed to verify the use of the Coastal Biosensor for Endocrine Disruption (C-BED) assay, previously developed to detect emerging contaminants and their effects on Mytilus edulis, on another mussel species, Mytilus galloprovincialis . Mussels were caged on St-Florent harbor (contaminated) and on Revellata Bay (reference) for three months. A classical multibiomarkers approach was coupled to the C-BED assay. The results of both approaches were analysed using the Integrated Biomarkers Responses (IBR) and compared to each other. Both approaches demonstrated a higher contamination and probable endocrine disruption of mussels in St-Florent, compared to the reference station. These results confirm that the C-BED assay provides an innovative method to expand our ability to detect emerging contaminants. Highlights: C-BED assay provides an innovative method to monitor for chemicals. There is a probable endocrine disruption of mussels in St. Florent. Both classical multibiomarkers approach and transcriptomic approach demonstrate a higher contamination in St. Florent. The use of the C-BED assay is validated on a new specie, Mytilus galloprovincialis .